The influence of electronic payment methods on tax compliance - Hamza, Randa Abd Elhamied Mohammed; Alnor, Nasareldeen Hamed Ahmed; Eisa, Mohamed Ishag Abdelrahman; Alhebri, Adeeb; Eltahir, Ibrahim Ahmed Elamin (International Journal of Innovative Research and Scientific Studies, 2025)
Financial transactions have undergone a revolution with the introduction of electronic payment technologies, which offer businesses and individuals more convenience, efficacy, and efficiency. However, this change has more ramifications than just efficiency and ease, particularly in terms of tax compliance. The purpose of this paper is to comprehend how electronic payment methods affect taxpayer compliance behavior. This article examines the several ways that electronic payment systems affect tax compliance, based on a thorough examination of the body of research in this area. It looks at elements that may lead to higher rates of tax compliance, such as accountability, openness, and the convenience of record-keeping made possible by electronic payment systems. The review also explores the psychological dimensions of tax compliance, looking at how taxpayers' attitudes and behaviors in the technological age are impacted by the convenience and fairness of electronic payment systems. In the context of tax compliance, this article highlights the dangers and obstacles that come with electronic payment systems, including data security concerns, privacy issues, and the digital divide. This paper offers insights into the relationship between electronic payment methods and tax compliance behavior in the digital era by critically analyzing existing studies. Our research indicates that, when it comes to creating efficient tax laws and enforcement tactics for the digital era, electronic payment systems and tax compliance are positively correlated. The research presented in this paper advances our knowledge of the factors influencing taxpayer behavior in the context of digital finance.